TEKNIK STERILISASI EKSPLAN TUNAS KENTANG GRANOLA KEMBANG (Solanum Tuberosum L.) UNTUK KULTUR IN VITRO - Syarif Hamdani; Delima Nugraha; Tiara Berliana; Umi Baroroh (Department of Chemistry, Faculty of Sciences and Informatics, Jenderal Achmad Yani University, 2020)
Potato (Solanum tuberosum L.) is a plant that widely used, both fresh and processed. However, the productivity of this plant is still low because the quality of seeds is still limited and is not good enough. The cultivar of granola kembang is potential to be developed because of the short harvest life and high yield. In vitro propagation through tissue culture can be done to produce high-quality seeds. The success of tissue culture is strongly influenced by explant sterilization techniques. Bacterial, fungal, and browning contamination can interfere with the process of culture propagation. In this study, six sterilization techniques were applied to potato shoot explants to get the right sterilization techniques for in vitro culture of potato. Various combinations of sterilant and their order of use are also used. Growth of stem length and number of leaves was also investigated for four weeks after planting (WAP). The results showed that sterilization using Tween-20, benomyl 50%, and agrimycin outside LAF and NaOCl 15% (v/v), NaOCl 10% (v/v), and alcohol 70% inside LAF could produce the highest percentage of sterile explant, 70%, compare to other techniques. Nevertheless, the sterilization technique used in this study did not affect the acceleration of stem growth and the number of leaves. Keywords: granola kembang, in vitro, potato, sterilization, tissue culture